Whole Genome Sequencing in the Management of Non-Tuberculous Mycobacterial Infections - Dohál, Matúš; Porvazník, Igor; Solovič, Ivan; Mokrý, Juraj (Microorganisms (Basel), 2021)
Infections caused by non-tuberculous mycobacteria (NTM) have been a public health problem in recent decades and contribute significantly to the clinical and economic burden globally. The diagnosis of infections is difficult and time-consuming and, in addition, the conventional diagnostics tests do not have sufficient discrimination power in species identification due to cross-reactions and not fully specific probes. However, technological advances have been made and the whole genome sequencing (WGS) method has been shown to be an essential part of routine diagnostics in clinical mycobacteriology laboratories. The use of this technology has contributed to the characterization of new species of mycobacteria, as well as the identification of gene mutations encoding resistance and virulence factors. Sequencing data also allowed to track global outbreaks of nosocomial NTM infections caused by M. abscessus complex and M. chimaera. To highlight the utility of WGS, we summarize recent scientific studies on WGS as a tool suitable for the management of NTM-induced infections in clinical practice.